Law and order in Sung China - McKnight, Brian E. (Cambridge studies in Chinese history, literature, and institutions, 1992)
This study examines law enforcement within the context of Sung society. Professor McKnight shows that the group of criminals who were the core of the habitual criminal group in Sung China were young unattached males with few lifeskills. What became of the criminal after capture and conviction is also an important aspect of this study, which addresses basic questions in Chinese punishment. This work is the first comprehensive study of law enforcement in traditional China. The depth and rigour to which the subject is treated would make it most appropriate for scholars in legal history and East Asian studies